2022
DOI: 10.3390/jcm11061542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iloprost on Oxygenation during One-Lung Ventilation in Patients with Low Diffusing Capacity for Carbon Monoxide: A Randomized Controlled Study

Abstract: The protective mechanism of hypoxic pulmonary vasoconstriction during one-lung ventilation (OLV) is impaired in patients with a low diffusing capacity for carbon monoxide (DLCO). We hypothesized that iloprost inhalation would improve oxygenation and lung mechanics in patients with low DLCO who underwent pulmonary resection. Forty patients with a DLCO < 75% were enrolled. Patients were allocated into either an iloprost group (ILO group) or a control group (n = 20 each), in which iloprost and saline were inha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Our results indicate that ILO positively affected alveolar ventilation in the supine position, which is consistent with the results of previous studies [ 9 , 10 ]. While the etCO 2 of the two groups remained unchanged since we adjusted the respiratory rate to maintain the parameter at its target range throughout the measurement periods, significant increases were observed in PaCO 2 of the control group, leading to an increase in the alveolar dead space.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results indicate that ILO positively affected alveolar ventilation in the supine position, which is consistent with the results of previous studies [ 9 , 10 ]. While the etCO 2 of the two groups remained unchanged since we adjusted the respiratory rate to maintain the parameter at its target range throughout the measurement periods, significant increases were observed in PaCO 2 of the control group, leading to an increase in the alveolar dead space.…”
Section: Discussionsupporting
confidence: 94%
“…Inhaled ILO selectively dilates pulmonary terminal capillaries surrounded by alveoli, resulting in increased pulmonary blood flow in the well-ventilated areas of the lung [ 12 ]. Hence, the effects of ILO were recently investigated by anesthesiologists as a potential rescue drug for hypoxia during OLV in thoracic surgery [ 8 , 9 , 10 ]. Indeed, previous studies indicated that the selective ILO administration to the ventilated lung during OLV induced a decrease in ventilation/perfusion (V/Q) mismatch and improved oxygenation [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radial artery catheterization was performed for continuous pressure monitoring, and 7 Fr central venous catheterization was applied. Anesthesia was maintained with an inhalation anesthetic agent (sevoflurane or desflurane) at a 0.9–1.2 age-adjusted minimal alveolar concentration, combined with a continuous intravenous infusion of remifentanil to target a bispectral index of 40–60 [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%